The Influence of Interest in the Use of Sia E-Commerce on The Tiktok Application Using the Method of Technology Acceptance Model (TAM) - Hamdani, Ikhwan; Murdiansyah, Isnan (Journal of Economics Education and Entrepreneurship, 2023)
Technological developments are currently increasingly rapid from year to year, making technology the main resource in all aspects of life. In all aspects or jobs, humans require the availability of technology to complete each job efficiently. Moreover, currently online transactions use the internet, one of which is using the TikTok application, where in this application someone can carry out online transactions such as promotions, selling, purchasing goods and services. The aim of this research is to find out how much influence subjective norms, perceived ease, usefulness and complexity have on interest in using e-commerce-based AIS on the TikTok application, then acceptance using the Technology Acceptance Model (TAM) method. For the population in this study, researchers took students from the Uin Maulana Malik Ibrahim Malang Accounting study program who had taken the Accounting Information Systems course and had used the Tiktok application several times. The sample in this study was 60 respondents and distributed questionnaires using random selection techniques without any engineering. Then the data is processed into an SPSS application and then the results of the processed data show that subjective norms, perceptions of ease, usefulness and complexity have a significant positive effect on the intention to use e-commerce based AIS on the TikTok application using the Technology Acceptance Model (TAM) method.